G protein-coupled receptor GPR68 inhibits lymphocyte infiltration and contributes to gender-dependent melanoma growth - Ye, Shangmei; Zhu, Yunfeng; Zhong, Dongmei; Song, Xiaodong; Li, Jialin; Xiao, Fang; Huang, Zhilei; Zhang, Wenjie; Wu, Mingyue; Zhang, Kangdi; Xiang, Fu-li; Xu, Jie (Frontiers in Oncology, 2023)
Melanoma is a common and aggressive type of skin cancer with rising incidence rate globally. Gender is one of the determining factors, and overall males have a higher risk of developing melanoma as well as worse prognosis. Biological difference of sex hormone, tumor microenvironment and immune system in males and females contribute to disparity of melanoma outcome, but the underlying mechanisms remain unclear. In the present study, we found that the G protein-coupled receptor GPR68 is required for melanoma growth in males but dispensable in females. GPR68 is expressed and functional in B16-F10 melanocytes, but the activity of the receptor does not directly contribute to proliferation and migration of the cells. GPR68 inhibits infiltration of CD45+ lymphocytes, CD8+ T cells and NK cells in melanoma in male mice, but has no apparent effect in females. Furthermore, GPR68 functionally inhibits the surface expression of IFNγ by the infiltrating CD8+ T cells and NK cells in male mice but not in females. Our results show the gender-dependent modulatory effect of GPR68 on tumor-infiltrating immune cells and their tumor-killing capacity. Since GPCRs are more feasible to develop small molecule drugs compared to transcription factors, our study demonstrates the potential of GPR68 as a novel druggable therapeutic target for melanoma in male patients.